Motivation, Knowledge and Attitude Toward the Role of Cadres in Improving Posyandu Services in the Work Area of Lembang Puskesmas, Majene Regency - Muh Fauzar Al-Hijrah; Alma Masri; Muhammad Irwan; Muhammad Hosni Mubarak (Politeknik Karya Persada Muna, 2022)
Background: of Posyandu being managed by a puskesmas cannot be separated from the role of the community through the presence of cadres. The role of Posyandu cadres is to bring the needs of health services closer to the community. To improve the performance of posyandu cadres, it is necessary to look at the variables related to posyandu cadres' performance. The aim of the researcher was to determine the relationship between motivation, knowledge and attitude with the role of cadres in improving posyandu services in the working area of the Lembang Health Center.Method: Quantitative research method using a cross sectional approach with a sample of 55. The measuring instrument uses a questionnaire with a checklist method.Result: The results showed 29 respondents (52.7%) with good motivation, knowledge and attitude with the role of cadres in improving posyandu services, while as many as 26 respondents (47.3%) had less motivation, knowledge and attitudes with the role of cadres in improving posyandu service. Conclusions: The results of the Chi Squere test obtained a P value = 0.000 <0.05, it can be concluded that there is a relationship between motivation, knowledge and attitude with the role of cadres in improving posyandu services in the working area of the Lembang Public Health Center, Majene Regency.Keywords: Posyandu, cadres, attitude, knowledge, motivation